Prescribing Phones to Address Health Equity Needs in the COVID-19 Era: The PHONE-CONNECT Program - Kazevman, Gill; Mercado, Marck; Hulme, Jennifer; Somers, Andrea (JMIR Publications, 2021)
Vulnerable populations have been identified as having higher infection rates and poorer COVID-19-related outcomes, likely due to their inability to readily access primary care, follow public health directives, and adhere to self-isolation guidelines. As a response to the COVID-19 pandemic, many health care services have adopted new digital solutions, which rely on phone and internet connectivity. However, persons who are digitally inaccessible, such as those experiencing poverty or homelessness, are often unable to use these services. In response to this newly highlighted social disparity known as "digital health inequity," emergency physicians at the University Health Network in Toronto, Canada, initiated a program called PHONE-CONNECT (Phones for Healthier Ontarians iN EDs - COvid NEeds met by Cellular Telephone). This novel approach attempts to improve patients' access to health care, information, and social services, as well as improve their ability to adhere to public health directives (social isolation and contact tracing). Although similar programs addressing the same emerging issues have been recently described in the media, this is the first time phones have been provided as a health care intervention in an emergency department. This innovative emergency department point-of-care intervention may have a significant impact on improving health outcomes for vulnerable people during the COVID-19 pandemic and beyond.